2022
DOI: 10.33546/bnj.1735
|View full text |Cite
|
Sign up to set email alerts
|

Nurse workforce scheduling: A qualitative study of Indonesian nurse managers’ experiences during the COVID-19 pandemic

Abstract: Background: The increase in COVID-19 cases in Indonesia has resulted in changes in the hospital workflow, including the staffing process and scheduling, especially in the isolation units. Nurse managers are working hard in the scheduling system to ensure high-quality care is provided with the best human resources. Objective: This study aimed to explore the experiences of nurse managers in managing staff nurses’ work schedules during the COVID-19 pandemic. Methods: A qualitative descriptive design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…The current findings echo those in a study of Indonesian nurse mangers during the COVID-19 pandemic ( Sugianto et al, 2022 ). The authors reported a reduction in nursing staff and an increase in the number of patients during the pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current findings echo those in a study of Indonesian nurse mangers during the COVID-19 pandemic ( Sugianto et al, 2022 ). The authors reported a reduction in nursing staff and an increase in the number of patients during the pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…The authors reported a reduction in nursing staff and an increase in the number of patients during the pandemic. The nurse managers described feeling exhausted and stated that patient care was not ideal due to lack of staff ( Sugianto et al, 2022 ). This aligns with the present study in which participants also experienced exhaustion and staffing shortages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no longer shift in the nurse's schedule adjustment, the participants keep the nurses from getting tired and things that are also taken into consideration in meeting the needs of existing staff must be adjusted to the capabilities of a country or region. So there will be differences to fulfill needs of the country in each country or region (Sugianto et al, 2022).…”
Section: Sub-theme B: Schedulling During Pandemicmentioning
confidence: 99%
“…However, nurse leaders’ roles face complex challenges (Sugianto et al, 2022 ), including ethical challenges in their daily practice, such as complaints, critical decision-making, patient and family demands, and conflicts between staff (Aitamaa et al, 2016 ), which require an excellent strategy to respond appropriately. Thus, ethical leadership is crucial, aligning nursing fundamentals with ethical nursing behavior and positively impacting clinical practice (Barkhordari-Sharifabad et al, 2018 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%